HERMENEUTIKA HADIS ALA FATIMA MERNISSI - Muniroh Muniroh (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
Hermeneutics is a new method in understanding and meaning of the hadiths. It used by some contemporary moslem scholars. One of them is Fatima Mernissi. She concentrates to misoginic hadiths that discriminate women. In this article, the author tries to see her hermeneutics methodology. The methodology that is offered by Fatima Mernissi in studying hadith is double investigation with psycho-history as her approach. There are two steps in her method, that are historical aspect and methodology aspect. The first step is analyzing situation and condition that happen when hadith released and then, analyzing about the first transmitter, when, why and to whom that hadith is released.